2001
DOI: 10.1046/j.1469-1809.2001.6520111.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Parkinsonism: a review

Abstract: Idiopathic Parkinson's disease (IPD), a progressive neurodegenerative disorder, is a common cause of disability. No current therapies modify disease progression. The pathological hallmarks are the presence of Lewy bodies and massive loss of dopaminergic neurons in the pars compacta of the substantia nigra. Two genes (SNCA and parkin) as well as two gene loci have now been implicated in the pathogenesis of familial PD. These represent significant progress in our understanding of the disease, considering the rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 94 publications
(112 reference statements)
1
32
0
1
Order By: Relevance
“…Recent molecular studies have uncovered several genes whose mutations produce familial PD transmitted as disorders with Mendelian inheritance [34][35][36] and several polymorphisms that are associated to a increased risk for sporadic PD. 37 There are no, however, studies related to the genetic mechanisms that control for the diversity of the clinical symptoms present in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular studies have uncovered several genes whose mutations produce familial PD transmitted as disorders with Mendelian inheritance [34][35][36] and several polymorphisms that are associated to a increased risk for sporadic PD. 37 There are no, however, studies related to the genetic mechanisms that control for the diversity of the clinical symptoms present in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The gene for one rare autosomal recessive form of PD, which maps to chromosome 1p35-p36, has been cloned and found to code for the PINK1 (PTEN-induced kinase) protein, a kinase localized in the mitochondrion (221). A more common autosomal recessive locus, the parkin gene on chromosome 6q25.2-27, is a E3 ubiquitin ligase (228). Genetic inactivation of parkin in the mouse resulted in nigrostriatal defects associated with a decreased abundance of several mitochondrial proteins including the E1α subunit of pyruvate dehydrogenase, the 24-and 30-kDa subunits of complex I and the Vb subunit of complex IV and a general decrease in mitochondrial state III respiration.…”
Section: The Mitochondrial Etiology Of Degenerative Diseasesmentioning
confidence: 99%
“…Although the etiological causes of PD have not been fully elucidated, studies have identified major risk factors that include aging, exposure to environmental hazards, and genetic predisposition (1)(2)(3)(4)(5)(6). Under these pathological conditions, the expression of inducible NO synthase may be induced in glia (especially astrocytes and microglia) by inflammatory mediators (7).…”
Section: Parkinson Disease (Pd)mentioning
confidence: 99%